Reflective Writing in Teacher Education in China: Insights from Systemic Functional Linguistics - Joshua M Schulze; Anne C Ittner (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
This article aims to demonstrate the application of theory to teaching practice by examining how two teacher educators drew upon systemic functional linguistics (SFL) as a pedagogical and analytical tool to inform their teaching of reflective writing to Mandarin-dominant teacher candidates enrolled in an ESOL course within an educator preparation program at a university using English Medium Instruction (EMI) in China. First, the authors describe how they incorporated the SFL appraisal framework into their teaching to bring their multilingual student writers’ attention to the language of evaluation as they prepared to construct reflective language learning autobiographies. Second, the authors demonstrate how SFL-informed text analysis of the appraisal resources used within students’ written reflections deepened their understanding of their students’ reflective writing practices and informed their teaching and course development. The article concludes with suggestions for using the SFL appraisal framework to support the reflective writing of their multilingual teacher candidates.